Productivity Effects of Land Rental Markets in Ethiopia : Evidence from a Matched Tenant-Landlord Sample - Deininger, Klaus; Ali, Daniel Ayalew; Alemu, Tekie (2012)
As countries increasingly strive to transform their economies from agriculture-based into a diversified one, land rental will become of greater importance. It will thus be critical to complement research on the efficiency of specific land rental arrangements -- such as sharecropping -- with an inquiry into the broader productivity impacts of the land rental market. Plot-level data for a matched landlord-tenant sample in an environment where sharecropping dominates allows this paper to explore both issues. The authors find that pure output sharing leads to significantly lower levels of efficiency that can be attenuated by monitoring while the inefficiency disappears if inputs are shared as well. Rentals transfer land to more productive producers but realization of this productivity advantage is prevented by the inefficiency of contractual arrangements, suggesting changes that would prompt adoption of different contractual arrangements could have significant benefits.